Inhibition of adrenal steroidogenesis and heat shock protein 70 induction in neonatally feed restricted broiler chickens under heat stress condition. - Idrus, Zulkifli; Soleimani Farjam, Abdoreza; Khalil, M.; Omar, Abdul Rahman; Abdul Rahim, Raha (Verlag Eugen Ulmer, 2011)
This study was conducted to determine the roles of plasma corticosterone concentration (CORT) and heat shock protein 70 (Hsp70) expression in the acquisition of thermotolerance in broiler chickens subjected to neonatal feed restriction.Equal numbers of chicks were divided into one of the four feeding regimens: ad libitum (control), 60% feed restriction on days 4, 5 and 6 (FR60), 60% feed restriction on days 4, 5 and 6 + 1500 mg/kg metyrapone (FR60M) and 60% feed restriction on days 4, 5 and 6 + 1500 mg/kg quercetin (FR60Q). From 35 to 42 days of age, all birds were exposed to 37 ± 1°C and 70-80% relative humidity for 3 h/day.